Overview on Cognitive and Social Childhood Development: Implications and Policies for Early Childhood Development (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Childhood Development refers to the physical, cognitive, linguistic, and socio-emotionaldevelopment of a child from the prenatal stage up to age eight. This development happens in a variety ofsettings (homes, schools, health facilities, community-based centers) and involves a wide range ofactivities from child care to nutrition to parent education. Providers of services can include public,private, and non-governmental agencies. Early Childhood Development encompasses a number ofdistinct sub-stages, each of which presents particular needs Pregnancy and pre-natal prenatal care,attended births, registration, postnatal care 0 to 3 parent education, early stimulation and nutritioninterventions, home-based care, crèches 3 to 6 parent education, preschool 6 to 8 transition to formaleducation, improved early primary school From a development point of view, children who come fromthe most vulnerable and disadvantaged backgrounds need good-quality services and care the most,including children with special needs for early childhood development. To ensure a nation‘s childrendevelop well, adequate investment in early childhood development is essential.